COMMUNICATION SKILLS: FACILITATING STUDENTS’ INVISIBLE BUT SIGNIFICANT SKILLS TO IMPROVE HEALTH OUTCOMES - Hikmawati Nurrokhmanti,; Astrid Pratidina Susilo; Rosaria Indah; Mora Claramita (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2022)
Background: Communication skills are the core skills throughout medical professional life and embedded with cultural factors. Although students have learned communication skills in the undergraduate education, adequate training during clinical rotation and continuing professional development is necessary. Facilitating the students to build partnership relationship in the communicating with patients is challenging, considering its contexts, facilities, and opportunities. The influence of student-teacher relations in this hierarchical context is also influential. Gaps: Facilitating partnership communication skill requires blending two paradigms: medical knowledge and communication. These complex skills can be optimally facilitated by using specific strategies such as role-play, simulated patient (SP), and real-case encounter. Thus, the communication skills curriculum needs a comprehensive program planning, preparation on the students’ ability to be able to receive feedback and reflect upon it, simulated patients’ contribution for students training, and teachers to provide effective feedback.Recommendation: Facilitating students' communication skills needs 'two to tango,' combining between mastery of medical knowledge and partnership communication. A better communication curriculum should consider incorporating cultural competencies and applying the principles in effective training course design such as authenticity, variability, gradually from simple to complex, integrated, and scaffolding by specific evidence. Thus, should be supported by a good faculty development program that will facilitate safe environment and constructive feedback. In addition, the need for simulated patients or even now, a virtual patient, is inevitable.